Concentration block. multiple hybridization in the fragmentary city (2008)
The text is synthesized from the university project “Concentration Block- Multiple Hybridization in the fragmentary City”. This exercise consists on an architectural project developed from an inquiry about the contemporary city, and its location is proposed in Bogotá city, as an example. The project is a critical exercise about the sprawl urban expansion which effect disables the possibility of improvement of collective transport systems, increases city building costs, magnifies the social fracture in the territory and intensifies the environmental emergency caused by the fumes of vehicles that must carry out exhausting itineraries. The hybrid project answers to these problems with more inhabitants densification and typological diversity in housing as a reflection of social diversity; more presence and variety of urban program to endow it of metropolitan character; environmental considerations that tend to the rational use of the energies.